2011
DOI: 10.1002/jcb.23277
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of p57kip2 promotes cell invasion via LIMK/cofilin pathway in human nasopharyngeal carcinoma cells

Abstract: The members of Rho family are well known for their regulation of actin cytoskeleton to control cell migration. The Cip/kip members of cyclin-dependent (CDK) inhibitors have shown to implicate in cell migration and cytoskeletal dynamics. p57(kip2) , a CDK inhibitor, is frequently down-regulated in several malignancy tumors. However, its biological roles in human nasopharyngeal carcinoma (NPC) cells remained to be investigated. Here, we found p57(kip2) has nuclear and cytoplasm distributions and depletion of end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 34 publications
1
13
0
Order By: Relevance
“…Previous studies have shown that actin cytoskeleton rearrangement induced by ROCK activation requires a cyclic activation and inactivation of cofilin, which is regulated by LIMK-dependent phosphorylation [22]. Our data indicates that leptin rapidly activates Rho GTPases, leading to LIMK1 and cofilin phosphorylation.…”
Section: Resultssupporting
confidence: 58%
“…Previous studies have shown that actin cytoskeleton rearrangement induced by ROCK activation requires a cyclic activation and inactivation of cofilin, which is regulated by LIMK-dependent phosphorylation [22]. Our data indicates that leptin rapidly activates Rho GTPases, leading to LIMK1 and cofilin phosphorylation.…”
Section: Resultssupporting
confidence: 58%
“…LIMK1 is highly expressed in invasive breast cancer cell lines and invasive tumors (7), suggesting a pro-tumorigenic function of LIMK. In support of this, the LIMK pathway has been shown to have a major role in cell migration and invasion (8), as well as tumor growth and metastasis (7). This study, for the first time, shows that LKB1 inhibits LIMK phosphorylation to regulate cofilin functions.…”
Section: Discussionmentioning
confidence: 55%
“…p21-activated kinase (PAK), 2 a downstream effector of Rac and Cdc42, is linked to cancer. High expression of PAK is detected in several breast tumor types, and activation of PAK leads to increased DNA synthesis, cell proliferation, anchorage-independent growth (7), and tumor growth (8). Moreover, PAKs phosphorylate and activate LIM kinase (LIMK), leading to increased phosphorylation of cofilin, which is important in regulating actin turnover.…”
mentioning
confidence: 99%
“…Recent studies have shown that CDKs and their cyclin family are important for cell migration in several types of tumors. [26][27][28][29] However, direct evidence demonstrating the relationship between expression of CDK11 and migration and invasion of cancer cells is lacking. We assessed whether knockout of CDK11 by CRISPR-Cas9 transfection could affect the migratory activity of osteosarcoma cells using a wound healing assay.…”
Section: Cdk11 Knockout Suppressed the Migratory Activity Of Osteosarmentioning
confidence: 99%